Crystal Structure and Switchable Dielectric Properties of Singly Protonated Homopiperazinium Perchlorate - Sui, Yan; Hu, Rong-Hua; Luo, Zhi-Gang; Wen, Ji-wu; Zhong, Long-Jin (Asian Journal of Chemistry, 2015)
Singly protonated homopiperazinium perchlorate (1) has been synthesized and characterized by single-crystal X-ray diffraction, IR, elemental analysis, DSC and temperature-dependent dielectric analysis. Compound 1 crystallizes in orthorhombic space group Pbca, their homopiperazinium cations are arranged in almost identical orientation by the parallel and nearly ideal linear N-H···N hydrogen bond chains. Very large dielectric change between high and low dielectric states is found at about 400 K due to reversible first-order phase transition. It is the first time that singly protonated homopiperazinium perchlorate is found to be a switchable dielectric material with high phase transition temperature and large dielectric change between high and low dielectric states.